FoxP3, CTLA-4, and IDO in Canine Melanocytic Tumors. Issue 1 (January 2021) - Porcellato, Ilaria; Brachelente, Chiara; Cappelli, Katia; Menchetti, Laura; Silvestri, Serenella; Sforna, Monica; Mecocci, Samanta; Iussich, Selina; Leonardi, Leonardo; Mechelli, Luca
Despite promising immunotherapy strategies in human melanoma, there are few studies on the immune environment of canine melanocytic tumors. In humans, the activation of immunosuppressive cell subpopulations, such as regulatory T cells (Tregs) that express forkhead box protein P3 (FoxP3), the engagement of immunosuppressive surface receptors like cytotoxic T lymphocyte antigen (CTLA-4), and the secretion of molecules inhibiting lymphocyte activation, such as indoleamine-pyrrole 2, 3-dioxygenase (IDO), are recognized as immunoescape mechanisms that allow tumor growth and progression. The aim of our study was to investigate the expression of these immunosuppression markers in canine melanocytic tumors and to postulate their possible role in melanoma biology and progression. Fifty-five formalin-fixed, paraffin-embedded canine melanocytic tumors (25 oral melanomas; 20 cutaneous melanomas; 10 cutaneous melanocytomas) were selected to investigate the expression of FoxP3, CTLA-4, and IDO by immunohistochemistry and RT-qPCR (real-time quantitative polymerase chain reaction). All of the tested markers showed high gene and protein expression in oral melanomas and were differently expressed in cutaneous melanomas when compared to their benign counterpart. IDO expression was associated with an increased hazard of death both in univariable and multivariable analyses ( P < .05). FoxP3 protein expression >6.9 cells/HPF (high-power field) was an independent predictor of death ( P < .05). CTLA-4 gene and protein expressions were associated with a worse prognosis, but only in the univariable analysis ( P < .05). FoxP3, CTLA-4, and IDO likely play a role in canine melanoma immunoescape. Their expression, if supported by future studies, could represent a prognostic tool in canine melanoma and pave the way to future immunotherapeutic approaches in dogs.